The influence of different types of alcohol on the cellular link of immunity in infertile men - Vorontsova, L. L.; Kovalenko, V. A.; Kozachuk, O. S.; Воронцова, Лоліта Леонідівна; Коваленко, Вікторія Анатоліївна; Козачук, Олександр Сергійович (Barcelona : Barca Academy Publishing, 2024)
The relationship between changes in semen parameters in the presence of sperm DNA fragmentation in men of reproductive age with impaired reproductive function was investigated. It has been established that changes in semen analysis indicate the presence of astheno-, oligo- and teratozoospermia, dyskinesis, and are dependent on the level of sperm DNA fragmentation. Thus, the more severe the changes in the key parameters of the spermogram, the greater the probability that the frequency of sperm DNA fragmentation will be higher than normal.
Keywords: male infertility; the degree of immunological disorders; non-specific immunity; semen analysis